Identification and characterization of a special type of subnuclear structure: AGGF1‐coated paraspeckles. Issue 6 (24th May 2022) - Zhao, Jinyan; Xie, Wen; Yang, Zhongcheng; Zhao, Miao; Ke, Tie; Xu, Chengqi; Li, Hui; Chen, Qiuyun; Wang, Qing K.
Abstract: AGGF1 is an angiogenic factor with G‐Patch and FHA domains 1 described by our group. Gain‐of‐function mutations in AGGF1 cause Klippel–Trenaunay syndrome, whereas somatic loss‐of‐function mutations cause cancer. Paraspeckles are small membraneless subnuclear structures with a diameter of 0.5–1 μm, and composed of lncRNA NEAT1 as the scaffold and three core RNA‐binding proteins NONO, PSPC1, and PSF. Here, we show that AGGF1 is a key regulatory and structural component of paraspeckles that induces paraspeckle formation, forms an outside rim of paraspeckles, wraps around the NONO/PSF/PSPC1/ NEAT1 core, and regulates the size and number of paraspeckles. AGGF1‐paraspeckles are larger (>1 μm) than conventional paraspeckles. RNA‐FISH in combination with immunostaining shows that AGGF1, NONO, and NEAT1_2 co‐localize in 20.58% of NEAT1_2 ‐positive paraspeckles. Mechanistically, AGGF1 interacts with NONO, PSF, and HNRNPK, and upregulates NEAT1_2, a longer, 23 kb NEAT1 transcript with a key role in regulation of paraspeckle size and number. RNA‐immunoprecipitation shows that AGGF1 interacts with NEAT1, which may be another possible mechanism underlying the formation of AGGF1‐paraspeckles. NEAT1_2  knockdown reduces the number and size of AGGF1‐paraspeckles. Functionally, AGGF1 regulates alternative RNA splicing as it decreases the exon skipping/inclusion ratio in a CD44  model. AGGF1 is also localized in some nuclear foci without NEAT1 or NONO, suggesting that AGGF1 is an important liquid–liquid phase separation (LLPS) driver for other types of AGGF1‐positive nuclear condensates (referred to as AGGF1‐bodies). Our results identify a special type of AGGF1‐coated paraspeckles and provide important insights into the formation, structure, and function of paraspeckles.